Addressing health system barriers to access to and use of skilled delivery services: perspectives from Ghana. (30th March 2015) - Ganle, John Kuumuori; Fitzpatrick, Raymond; Otupiri, Easmon; Parker, Michael
Abstract: Poor access to and use of skilled delivery services have been identified as a major contributory factor to poor maternal and newborn health in sub‐Saharan African countries, including Ghana. However, many previous studies that examine norms of childbirth and care‐seeking behaviours have focused on identifying the norms of non‐use of services, rather than factors, that can promote service use. Based on primary qualitative research with a total of 185 expectant and lactating mothers, and 20 healthcare providers in six communities in Ghana, this paper reports on strategies that can be used to overcome health system barriers to the use of skilled delivery services. The strategies identified include expansion and redistribution of existing maternal health resources and infrastructure, training of more skilled maternity caregivers, instituting special programmes to target women most in need, improving the quality of maternity care services provided, improving doctor–patient relationships in maternity wards, promotion of choice, protecting privacy and patient dignity in maternity wards and building partnerships with traditional birth attendants and other non‐state actors. The findings suggest the need for structural changes to maternity clinics and routine nursing practices, including an emphasis on those doctor–patient relational practices that positively influence women's healthcare‐seeking behaviours. Copyright © 2015 John Wiley & Sons, Ltd.